Group Dynamics Conflict and Digital Interaction in the Hajj and Umrah Travel Industry in Jakarta - Indrajaya, Titus; Ariyanto, Yudhy; Noviyanti, Indra; Harharah, Muhammad (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study aims to analyze group dynamics, conflicts, and digital interactions in the Hajj and Umrah travel industry in Jakarta as a religious service-based organization operating under regulatory pressure and public expectations. The research focus is directed at the patterns of internal interaction of organizations, the forms and sources of conflicts, and the role of digital communication in daily operational activities. This research uses a descriptive, qualitative approach with a document review design, including the analysis of scientific articles, regulations, organizational reports, and other written sources relevant to the Hajj and Umrah travel industry. Data were analysed through data reduction processes, thematic coding, and narrative synthesis based on the framework of group dynamics, organizational conflicts, and digital interactions. The results of the study show that group dynamics in Hajj and Umrah travel organizations are fluctuating and influenced by service intensity, especially during congested periods. Conflicts arise in various forms, including interpersonal and intersectoral conflicts, and conflicts involving external parties, with the main sources coming from work coordination, public service pressures, and regulatory changes. Digital interaction is increasingly establishing itself as the dominant modality for organizational communication and coordination, while also serving as a context for the proliferation of disputes arising from miscommunication and temporal constraints. This study concludes that group dynamics and conflicts in the Hajj and Umrah travel industry are social processes that are inseparable from the context of religious services and organizational digital transformation.